Kompetensi dan Karakteristik Kepemimpinan Kepala Sekolah Islam Abad 21 - Sastradiharja, EE. Junaedi; Zairin, Gentiga Muhammad (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2023)
Becoming a headmaster of an Islamic school in 21st century is not an easy thing, it needs a strong capacity building of competence, leadership characteristics as well as attitudes and work maturity. The 21st century is a global competition century, which is different from previous centuries. In this century, everyone feels sophisticated, making this world feel narrower and limitless. The sophistication of Information and Communication Technology (ICT) has changed something that was previously difficult and considered impossible to happen, to become easy, fast and accurate. Islamic schools which have the function of educating the people, developing the character and spiritual intelligence of students, need to be led by headmasters who have the competence and leadership characteristics are needed in the 21st century. This research used the library research method, which was a research whose object is sought from various library information such as books, theses, dissertations, scientific journals, magazines, newspapers, and documents. The results of the study shown the competencies of 21st century Islamic school headmasters include: personality, managerial, entrepreneurial, supervision, social, digital and spiritual competencies. While the characteristics of 21st century Islamic school headmasters include: visionary, mastering digital technology and artificial intelligence, having integrity, reliable and tough, effective communication skills, inspirational, encouraging and motivating, decision making skills, always listening, creative and proactive, working professionally, charismatic or authoritative, competition understanding, focus on group work and strengths, build character, and excellent service.